Evaluation of Anti-Trypanosoma cruzi Activity of Chemical Constituents from Baccharis sphenophylla Isolated Using High-Performance Countercurrent Chromatography - Matheus L. Silva; Felipe S. Sales; Erica V. C. Levatti; Guilherme M. Antar; Andre G. Tempone; João Henrique G. Lago; Gerold Jerz (Molecules, 2023)
Endemic in 21 countries, Chagas disease, also known as American Trypanosomiasis, is a neglected tropical disease (NTD) caused by the protozoan parasite Trypanosoma cruzi. The available drugs for the treatment of this disease, benznidazole and nifurtimox, are outdated and display severe side effects. Thus, the discovery of new drugs is crucial. Based on our continuous studies aiming towards the discovery of natural products with anti-T. cruzi potential, the MeOH extract from aerial parts of Baccharis sphenophylla Dusén ex. Malme (Asteraceae) displayed activity against this parasite and was subjected to high-performance countercurrent chromatography (HPCCC), to obtain one unreported syn-labdane diterpene — sphenophyllol (1) — as well as the known compounds gaudichaudol C (2), ent-kaurenoic acid (3), hispidulin (4), eupafolin (5), and one mixture of di-O-caffeoylquinic acids (6–8). Compounds 1–8 were characterized by analysis of nuclear magnetic resonance (NMR) and mass spectrometry (MS) data. When tested against trypomastigote forms, isolated labdane diterpenes 1 and 2 displayed potent activity, with EC50 values of 20.1 μM and 2.9 μM, respectively. The mixture of chlorogenic acids 6–8, as well as the isolated flavones 4 and 5, showed significant activity against the clinically relevant amastigotes, with EC50 values of 24.9, 12.8, and 2.7 μM, respectively. Nonetheless, tested compounds 1–8 displayed no cytotoxicity against mammalian cells (CC50 > 200 μM). These results demonstrate the application of HPCCC as an important tool to isolate bioactive compounds from natural sources, including the antitrypanosomal extract from B. sphenophylla, allowing for the development of novel strategic molecular prototypes against tropical neglected diseases.